The Importance of Data: Developing Smart Asset Management Framework in IoT Era - Marga Gumelar* (Airlangga Development Journal, 2017)
Municipal assets become hard problems that lasted a long time. In the fiscal year 2015, from total asset amount of   Rp 2,048.88 trillion, the Audit Board of the Republic of Indonesia found some problems on the audit of the local government financial report that 1,010 issues were related to asset registration. There were also 48 problems related to unknown assets and potential losses of Rp 289,281.23 million. This paper aims to develop municipal asset management framework by focusing on asset inventory system through the application of information technology. A case study is presented based on the findings of the Audit Board of the Republic of Indonesia. The result is a practical asset inventory system framework   to   improve   current   asset   inventory  performance.   The   use   of information technology can support the improvement of municipal asset management. But the tools are not enough without collaboration with employees. Since some regions in Indonesia inadequately have information technology infrastructure facilities, such as internet access and electricity network, this framework has obvious limitation.